Development of pyrimidone D1 dopamine receptor positive allosteric modulators. (1st January 2021) - Luderman, Kathryn D.; Jain, Prashi; Benjamin Free, R.; Conroy, Jennie L.; Aubé, Jeffrey; Sibley, David R.; Frankowski, Kevin J.
Graphical abstract: Abstract: MLS1082 is a structurally novel pyrimidone-based D1-like dopamine receptor positive allosteric modulator. Potentiation of D1 dopamine receptor (D1R) signaling is a therapeutic strategy for treating neurocognitive disorders. Here, we investigate the relationship between D1R potentiation and two prominent structural features of MLS1082, namely the pendant N -aryl and C -alkyl groups on the pyrimidone ring. To this end, we synthesized 24 new analogues and characterized their ability to potentiate dopamine signaling at the D1R and the closely related D5R. We identified structure–activity relationship trends for both aryl and alkyl modifications and our efforts afforded several analogues with improvements in activity. The most effective analogues demonstrated an approximately 8-fold amplification of dopamine-mediated D1R signaling. These findings advance the understanding of structural moieties underlying the activity of pyrimidone-based D1R positive allosteric modulators.